Recent advances in diagnostic approaches for sub-arachnoid hemorrhage - Kumar, Ashish; Kato, Yoko; Hayakawa, Motoharu; Junpei, ODA; Watabe, Takeya; Imizu, Shuei; Oguri, Daikichi; Hirose, Yuichi (Asian Journal of Neurosurgery, 2011)
Sub-arachnoid hemorrhage (SAH) has been easily one of the most debilitating neurosurgical entities as far as stroke related case mortality and morbidity rates are concerned. To date, it has case fatality rates ranging from 32-67%. Advances in the diagnostic accuracy of the available imaging methods have contributed significantly in reducing morbidity associated with this deadly disease. We currently have computed tomography angiography (CTA), magnetic resonance angiography (MRA) and the digital subtraction angiography (DSA) including three dimensional DSA as the mainstay diagnostic techniques. The non-invasive angiography in the form of CTA and MRA has evolved in the last decade as rapid, easily available, and economical means of diagnosing the cause of SAH. The role of three dimensional computed tomography angiography (3D-CTA) in management of aneurysms has been fairly acknowledged in the past. There have been numerous articles in the literature regarding its potential threat to the conventional "gold standard" DSA. The most recent addition has been the introduction of the fourth dimension to the established 3D-CT angiography (4D-CTA). At many centers, DSA is still treated as the first choice of investigation. Although, CT angiography still has some limitations, it can provide an unmatched multi-directional view of the aneurysmal morphology and its surroundings including relations with the skull base and blood vessels. We study the recent advances in the diagnostic approaches to SAH with special emphasis on 3D-CTA and 4D-CTA as the upcoming technologies.
Keywords: Aneurysm; computed tomography angiography; subarachnoid hemorrhage